(untitled) (Research, Society and Development, 2022)
This article aims to share the experience of Rio Grande city, state of RS, with regard to the historical record of implementation, realization and execution of actions aimed at school Fistball. It is a descriptive study, based on the documental research in the news posted on the website of the Municipal Department of Education (SMEd) between the years 2013 and 2019. Data analysis took place from the perspective of content analysis and resulted in three categories of analysis: Disclosures of actions in Fistabll; Results of actions in Fistball carried out in the city; and Results of state competitions. Fistball is present in schools in Rio Grande in physical education classes, extra-class projects and sports competitions held both in the municipality and at the state level, thus integrating schools with other communities, groups and institutions. In addition, the organization and participation in sporting events, such as festivals and cups, shows how into physical education and in school culture as a whole this sport is, fact that was observed by the mobilization of different educational institutions participating in the reported actions. In this sense, it is clear that, despite being relatively recent, the work carried out has made Fistball not being a totally unknown sport anymore and becoming a popular practice in a considerable portion of schools of Rio Grande, writing thus, the success story of this practice consolidated at the school level.